Our experiences with development of digitised video streams and their use in animal-free medical education - Cervinka, Miroslav; Cervinková, Zuzana; Novák, Jan; Spicák, Jan; Rudolf, Emil; Peychl, Jan (ATLA. Alternatives to laboratory animals, 2004)
Alternatives and their teaching are an essential part of the curricula at the Faculty of Medicine. Dynamic screen-based video recordings are the most important type of alternative models employed for teaching purposes. Currently, the majority of teaching materials for this purpose are based on PowerPoint presentations, which are very popular because of their high versatility and visual impact. Furthermore, current developments in the field of image capturing devices and software enable the use of digitised video streams, tailored precisely to the specific situation. Here, we demonstrate that with reasonable financial resources, it is possible to prepare video sequences and to introduce them into the PowerPoint presentation, thereby shaping the teaching process according to individual students' needs and specificities.
Keywords: Education, Medical; Animal Testing Alternatives; Videotape Recording; videozáznam; studium lékařství; alternativy testů na zvířatech